Effect of mechanochemical treatment on VOPO4.2H2O to produce vanadyl pyrophospate catalysts - Yap, Taufiq Yun Hin; Wong, Yee Ching; Zainal, Zulkarnain; Hussein, Mohd Zobir (Malaysian Nuclear Society, 2009)
Two vanadly pyrophosphate catalysts were prepared via dihydrate route (VPD method) by appying mechanochemical treatment performed on VOPO42H2O in different duration of time.i.e 30 and 60 min in ethanol medium. Both catalysts with the unmilled catalyst produced were characterized by x-ray diffraction (XRD). chemical analysis, scanning electron microscopy (SEM) and temperature programmed reduction (H2-TPR). Catalytic evaluation for partial oxidation of n-butane to maleic anhydride (MA) was also being carried out using microreactor. XRD patterns of all VPO catalysts showed the main peaks of pyrophosphate phase. TPR profiles showed that the mechanochemical treated VPO catalyst for 30 min (VPDM30) removed the active oxygen species at lower temperature. Futhermore, from the catalytic test result, the graph of the catalytic performance as a funtion of the duration of mechanochemical treatment demonstrates that VPDM30 is the most active catalyst. This suggested that the mechanochemical treatment of the VOPO4 2H2O for the synthesis of pyrophosphate catalyst (VPDM30) is highly potential to enhance the catalytic properties for n-butane oxidation towards maleic anhydride.